Bezpieczeństwo żywnościowe krajów rozwijających się - Gulbicka, Bożena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Starving or permanently undernourished people was estimated at the beginning of the 21st century at 854 milion, 96 per cent of them lived in developing countries. The undernourishment so many people results from the low level of socio-economic development. The right of every human being to be free from hunger is not respected. The purpose of the study was to present the most important problems concerning undernourishment in the developing countries. The research was conducted on the basis of the information from the international organizations within the United Nations i.e. the Food and Agriculture Organization (FAO) and the World Health Organization (WHO). The article includes the conclusion that there are two ways leading to food security in the developing countries: development of agricultural and other productive sectors, it means improving the economic state of the country, easy access to education and medical services and at the same time external aid for the development and food aid for the people suffering from poverty and hunger.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 130-140